Total Synthesis of Natural Products At the Frontiers of Organic Chemistry - Li, Jie Jack.; Corey, E.J.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
'Total Synthesis of Natural Products' is written and edited by some of today's leaders in organic chemistry. Eleven chapters cover a range of natural products, from steroids to alkaloids. Each chapter contains an introduction to the natural product in question, descriptions of its biological and pharmacological properties and outlines of total synthesis procedures already carried out. Particular emphasis is placed on novel methodologies developed by the respective authors and their research groups. This text is ideal for graduate and advanced undergraduate students, as well as organic chemists in academia and industry.
Nominine -- Nakiterpiosin: A Novel C-nor-D-homosteroid -- The Kinamycins -- A Short Synthesis of Strychinine from Pyridine -- Bryostatin 7 -- Serratezomine A -- Hypocrellin/Cercosporin -- Total Synthesis of Phomactin A -- (+)-11,11'-Dideoxyverticillin A -- Retigeranic Acid -- Companadine A.
Keywords: Chemistry; Toxicology; Chemistry, Organic; Biochemistry; Chemistry; Organic Chemistry; Pharmacology/Toxicology.; Medicinal Chemistry